2008
DOI: 10.1136/thx.2007.081315
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of CPAP vs bilevel support in the treatment of obesity hypoventilation syndrome without severe nocturnal desaturation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
173
2
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(204 citation statements)
references
References 25 publications
16
173
2
13
Order By: Relevance
“…BMI also decreased slightly. Similar to our previous report, 31 no difference was found between the options of CPAP and BPAP in improving awake pCO 2 (p = 0.27) and SpO 2 nadir during sleep (p = 0.62) in the present study. EEG spectral analyses showed that the D/A ratio of EEG was significantly reduced during both sleeping and waking periods, indicating a generally faster, more activated EEG spectral profile following treatment ( Table 2).…”
Section: Resultssupporting
confidence: 81%
“…BMI also decreased slightly. Similar to our previous report, 31 no difference was found between the options of CPAP and BPAP in improving awake pCO 2 (p = 0.27) and SpO 2 nadir during sleep (p = 0.62) in the present study. EEG spectral analyses showed that the D/A ratio of EEG was significantly reduced during both sleeping and waking periods, indicating a generally faster, more activated EEG spectral profile following treatment ( Table 2).…”
Section: Resultssupporting
confidence: 81%
“…There is considerable evidence that CPAP use reduces cardiovascular morbidity, mortality, and road traffic accidents traffic consequences in patients with OSA. [18][19][20][21][22] Despite the severity of the consequences of OHS, CPAP may improve the symptoms and selected clinical variables of the disease [23][24][25][26] ; however, data showing positive effects on prospective cardiovascular or other variables are limited and prospective studies are awaited.…”
mentioning
confidence: 99%
“…No significant difference was seen in daytime PaCO 2 , weight loss, adherence to therapy or daytime sleepiness. The bi-level PAP therapy group reported better subjective sleep quality and performed better on a psychomotor vigilance task than the CPAP group [70].…”
Section: Bi-level Papmentioning
confidence: 99%
“…[50,[74][75][76] Bi-level PAP therapy is beneficial in preventing obstructive events, improving expiratory flow limitation and also improves tidal volume by providing inspiratory pressure support. Bilevel therapy when used long term has been shown to improve blood gases, quality of life and ventilator responsiveness to CO 2 [50,70,[77][78][79][80][81]. Bi-level PAP therapy unloads inspiratory muscles and has been shown to reduce diaphragmatic effort by nearly 40% [34].…”
Section: Bi-level Papmentioning
confidence: 99%
See 1 more Smart Citation